Identifying Financial Exclusion and Islamic Microfinance as An Alternative to Enhance Financial Inclusion - Hartomi Maulana; Khoirul Umam (International Journal of Islamic Business and Economics (IJIBEC))
Even though the banking industry is growing exponentially, but they are still out of reach from the hardcore poor. The population under poverty remains financially excluded from the mainstream banking facilities. The aim of this paper is to examine the main factors that hinder customers to access financing from mainstream banking in Indonesia province of East Java using Exploratory Factor Analysis (EFA). The study also attempts to identify the possibility of Islamic microfinance, in this case Baitul Maal Tamwil, (BMT) as role of model in integrating commercial and social seeking which can be used as one of an alternative platform to enhance financial inclusion.